Photosensitization of Colloidal TiO2 Semiconductor with Zinc Phthalocynine - GHANEM, RAED (Asian Journal of Chemistry, 2010)
Zinc-phtalocyanine with tyrosine substituents (ZnPcTyr) was attached to the surface of the colloidal nanocrystalline TiO2 via carboxylic acid group. The interaction of ZnPctyro with colloidal was studied by absorption and fluorescence spectroscopy. The apparent association constant for the association between ZnPcTyr and TiO2 is about 4.5 × 104 M-1 with a degree of association up to 90%. Presence of the tyrosine group in ZnPcTyr enhances the solubility of the dye in ethanol and decrease the aggregation behavior. Anchoring of the dye complex to the nanocrystalline TiO2 enables ultrafast injection of electrons from the excited state into the conduction band of TiO2 (completed in ca. 500 fs) which results in strong quenching of the singlet state of the ZnPcTyr and a maximum of incident photon to current efficiency (IPCE) is ca. 24% at 690 nm, the low IPCE is due to the surface aggregation and fast charge recombination. Photophysical properties of the zinc phthalocyanine and the transient spectra were also determined.